HARAPAN TERHADAP KEPUASAN DAN DAMPAKNYA PADA KELUHAN DAN LOYALITAS PELANGGAN (STUDI DI KFC AHMAD YANI) - Diky Murdoyo Rahadiarto (Journal of Business & Banking, 2012)
Kentucky Fried Chicken (KFC) is one of the successful companies in Indonesia. It can be proved by the data in top brand index from marketing magazine that put KFC in the first position. KFC succeeded in becoming the first position due to its ability to make customers more loyal forever. Some of the factors that make KFC selected by the subscribers, among others, is that KFC managed to be complied with the customers expectation. This is the factor to make its customers satisfied. It has been noted in the research that customer loyalty is the product ultimate purpose or service provider. The purpose of this research was to find out the influence of the customer expectation, customer satisfaction towards the customer complaints, and customer loyalty. The design of this study is by means of convenience sampling. The data were collected using questionnaire. The method analysis used in this research is Maximum Likely hood test using the program AMOS version 18.0. The results showed that the two hypotheses were accepted. Firstly, the customer expectation has a significant impact on the customer satisfaction and the second is that the customer satisfaction has a significant influence on customer loyalty.